Unlocking prevention: the role of health literacy in cervical cancer screening: community nursing perspective - Mohamed Amin, Shaimaa; Metwally El-Sayed, Mona; Hashem El-Monshed, Ahmed; Hussein Ramadan Atta, Mohamed (BMC nursing, 2025)
Introduction Cervical cancer presents a significant global public health challenge, particularly affecting low- and middle-income countries like Egypt. Despite the availability of effective screening methods such as Pap smears and HPV testing, the incidence of cervical cancer remains high in Egypt. Health literacy, which refers to the ability to access, understand, and utilize basic health information and services to make informed decisions, is crucial in influencing individuals’ health behaviors, including their participation in cancer screening programs. Objectives To examine the correlation between health literacy levels and cervical cancer screening behaviors among women. Methods This study employed a multi-site cross-sectional research design from September 2023 to January 2024. The research was conducted at four primary health care (PHC) facilities in the Damanhur district of Egypt. Three hundred fifty women participated in the study, completing a comprehensive questionnaire that included a Woman’s Social and Health Form, a Cervical Cancer Knowledge Scale, a Cervical Cancer Screening Behaviors Scale, and a Health Literacy Scale (HLS-SF12). Results The study revealed significant relationships between the importance of health literacy (HL) in understanding cervical cancer (CC) knowledge and screening behaviors among Egyptian women. A positive correlation was found between Knowledge and HL ( r = 0.507, p < 0.001). Conversely, perceived barriers negatively correlated with knowledge and HL ( r = -0.172, p < 0.05; r = -0.277, p < 0.01). The regression analysis revealed that higher levels of HL were significantly associated with greater knowledge about CC (B = 0.148, p < 0.001). Conversely, knowledge about CC was also found to be a strong predictor of higher HL levels (B = 1.205, p < 0.001). These results highlight the bidirectional relationship between HL and knowledge, where improvements in one can enhance the other. Conclusion Addressing misconceptions and increasing knowledge about the importance of regular screenings, mainly through accessible and culturally appropriate channels, could lead to an improved uptake of cervical cancer screening services. Overall, this study lays a foundation for future research to continue exploring ways to improve cervical cancer prevention and control efforts among women. Clinical trial number Not applicable.